METODE PEMBELAJARAN MULTISENSORI VAKT SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MEMBACA LANCAR SISWA KELAS II - Basam, Fajri; Sulfasyah, Sulfasyah (JRPD (Jurnal Riset Pendidikan Dasar), 2018)
Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk meningkatkan kemampuan membaca lancar melalui metode multisensori VAKT (Visual, Auditory, Kinesthetic, Tactile) pada siswa kelas II Sekolah Dasar. Penelitian ini dilaksanakan dalam dua siklus yang terdiri atas empat komponen utama:         1) Perencanaan, 2) Pelaksanaan tindakan, 3) Observasi, dan 4) Refleksi. Subjek penelitian adalah siswa kelas II sebanyak  49 orang siswa. Pengumpulan data menggunakan tes dan observasi. Analisis data yang digunakan adalah dengan analisis data kuantitatif deskriptif. Hasil penelitian menunjukkan rata-rata hasil tes membaca lancar siswa pada siklus I sebesar 59.32 mengalami peningkatan sebesar 77.64 dari skor maksimal 100. Sebesar 81.63% siswa telah mencapai kriteria ketuntasan minimal (KKM) pada siklus kedua. Hal ini menunjukkan indikator yang ditetapkan yaitu sebesar 80% siswa mencapai KKM telah tercapai. Dengan demikian metode pembelajaran multisensori VAKT dapat meningkatkan kemampuan membaca lancar siswa kelas II.This study is a classroom action research that aims to improve the ability to read fluently through VAKT multisensory method (Visual, Auditory, Kinesthetic, Tactile) in grade II  elementary school students.  The research was conducted in two cycles consisting of four main components, namely: 1) Planning, 2) Implementation of action, 3) Observation, and 4) Reflection.  The subjects of the study were the second grade students of 49 students.  Data collection using test and observation, while data analysis used is with descriptive quantitative data analysis.  The results showed the average of the results of students' reading tests on the first cycle of 59.32 has increased by 77.64 from a maximum score of 100.  A total of 81.63% of students have achieved minimal mastery criteria (KKM) in the second cycle.  This indicates that the indicator set by 80% of students reaching KKM has been achieved. Thus VAKT multisensory learning method can improve the ability to read fluently grade II students. This study is a classroom action research that aims to improve the ability to read fluently through VAKT multisensory method (Visual, Auditory, Kinesthetic, Tactile) in grade II  elementary school students.  The research was conducted in two cycles consisting of four main components, namely: 1) Planning, 2) Implementation of action, 3) Observation, and 4) Reflection.  The subjects of the study were the second grade students of 49 students.  Data collection using test and observation, while data analysis used is with descriptive quantitative data analysis.  The results showed the average of the results of students' reading tests on the first cycle of 59.32 has increased by 77.64 from a maximum score of 100.  A total of 81.63% of students have achieved minimal mastery criteria (KKM) in the second cycle.  This indicates that the indicator set by 80% of students reaching KKM has been achieved. Thus VAKT multisensory learning method can improve the ability to read fluently grade II students.